1981
DOI: 10.1007/bf00327354
|View full text |Cite
|
Sign up to set email alerts
|

A structural analysis of Balbiani ring DNA sequences in Chironomus tentans

Abstract: The Balbiani rings in the salivary gland polytene chromosomes of Chironomus tentans include the most active structural genes in this organ. Two of them (BR1 and BR2) contain repetitive sequences and are transcribed into giant RNA molecules. On Southern blots of restriction digests, we have identified fragments of genomic DNA which contain BR sequences. One of these fragments with a length of about 150 bp has been cloned and shown to hybridize preferentially to the BR1 transcription unit. Determination of its n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
22
1

Year Published

1982
1982
1984
1984

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 34 publications
4
22
1
Order By: Relevance
“…Southern analysis using that clone as probe revealed periodic "ladders" in genomic DNA lightly digested with various restriction enzymes, and thus indicated that the internal repeats of the BRc gene are tandemly organized. A similar, tandemly repetitive substructure has been demonstrated in the BRI gene of C. tentans (Degelmann and Hollenberg, 1981), and in its BRb homologue of C. thummi (Baumlein et al, 1982).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Southern analysis using that clone as probe revealed periodic "ladders" in genomic DNA lightly digested with various restriction enzymes, and thus indicated that the internal repeats of the BRc gene are tandemly organized. A similar, tandemly repetitive substructure has been demonstrated in the BRI gene of C. tentans (Degelmann and Hollenberg, 1981), and in its BRb homologue of C. thummi (Baumlein et al, 1982).…”
Section: Introductionsupporting
confidence: 60%
“…Parts of the dominant repeat units of BRI and BRb have been sequenced (Degelmann and Hollenberg, 1981;Baumlein et al, 1982), as has a variant of the BRc repeat (Wobus et al, 1980). We now report the complete sequence of the dominant BRc unit, which we have encountered in four tandem copies by extending our characterization of the previously isolated pCthBRc-19 clone.…”
Section: Introductionmentioning
confidence: 82%
“…It should be added that the nonrepetitive region ofthe major repeat unit in pCt 21 is almost identical to the short BR 1 sequence (147 bp) analyzed by Degelmann and Hollenberg (6). Our sequence differs at three base pair positions from that of Degelmann and Hollenberg.…”
Section: Construction Of 75smentioning
confidence: 62%
“…This sequence forms a nonrepetitive part of the major repeat unit in the present-day BR 2 gene. Recently, a short BR 1 specific sequence also has been analyzed by Degelmann and Hollenberg (6). We noted that this BR 1 sequence shows a high degree of sequence homology with the nonrepetitive region of the BR 2 major repeat unit.…”
mentioning
confidence: 86%
“…The BR genes contain the genetic information for large salivary secretory proteins (8,9), which are used to spin tubes housing the aquatic larvae. The principal structures of the BR 1 (10)(11)(12) and BR 2 (13-15) genes in C. tentans, the BR 2 gene in Chironomus pallidivittattus (16), and the BR b (17) and BR c (18) genes in Chironomus thummi have been revealed, and, in all cases, the genes consist of a large number of 150-to 300-base-pair (bp)-long repeat units that are tandemly repeated. All repeat units have one constant region (C region) and one subrepeat region (SR region),t the latter being formed by a number of subrepeats.…”
mentioning
confidence: 99%